Strengthening green transformational leadership through green organizational culture and green self-efficacy to improve employee green behavior in sustainable organization - Khalilah Daud Isaac Makhmut; Ainur Rahim Setiawan; Sarti Anjelika Manune (Annals of Human Resource Management Research, 2025)
Purpose: This study investigates the influence of green transformational leadership (GTL) on employee green behavior (EGB) in the hospitality sector of East Java, Indonesia, mediated by green self-efficacy (GSE) and green organizational culture (GOC). Addressing inconsistencies in prior research, the study aims to clarify how leadership and organizational factors collectively foster pro-environmental behaviors in sustainable tourism organizations. Research Methodology: This study used a quantitative explanatory survey involving 340 employees from 368 starred hotels in East Java. Samples were selected using the Slovin formula, and data were analyzed using PLS-SEM with SmartPLS 4.0 to examine GTL, GSE, GOC, and EGB relationships. Results: The study reveals three key findings: (1) GTL significantly enhances both GSE and GOC, with stronger effects on GOC (path coefficient = 0.852); (2) GSE and GOC partially mediate the relationship between GTL and EGB, with GOC exhibiting a stronger mediating role (path coefficient = 0.389); and (3) GTL directly influences EGB, though its indirect effects through mediators are more pronounced. Conclusions: The findings underscore the pivotal role of GTL in shaping employees' confidence and organizational culture to drive green behaviors. Organizations should prioritize leadership development and cultural initiatives to align sustainability goals with daily practices. Limitations: The study is geographically confined to East Java’s hospitality sector and relies on self-reported data, which may introduce bias. Future research could expand to other regions and industries while incorporating longitudinal designs. Contribution: This study advances theoretical understanding by integrating GSE and GOC as mediators in the GTL-EGB relationship. Practically, it offers actionable insights for fostering sustainable workplaces through leadership and cultural interventions.